Effect of ethanol extract from Karuk leaf (Piper sarmentosum Roxb.) on the growth of Malassezia furfur in vitro - Khusnul Khusnul; Asti Kusmayanti; Lia Aulia Rahman; Nuniek I Ratnaningtyas (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2020)
In Indonesia, there are numerous therapeutic plants found. Some of the plants used in herbal medicine are Karuk leaf (Piper sarmentosum Roxb.) belong to the Piperaceae family. Karuk leaf has chemical contents such as saponins, polyphenols, flavonoids, and essential oils and many tests are carried out on several bacteria, but testing of fungi is rarely studied. This study aims to determine the ethanol extract activities from karuk leaf in inhibiting the growth of the Malassezia furfur fungus and to determine its minimum inhibition by using the Kirby-Bauer method. The study was conducted by an experimental method of the M. furfur fungus using the Kirby-Bauer method. The ethanol extract from karuk leaf was made in various concentrations and tested on 0.5 McFarland fungus by diffusion on Sabouraud Dextrose Agar (SDA). The results of this analysis showed that the ethanol extract of Karuk leaf could inhibit the M. furfur fungus at a concentration of 30% by 5.3 mm, 40% by 6.6 mm, 50% by 7.6 mm, 60% by 11.3 mm, 70% by 12.5 mm, 80% by 15.6 mm, 90% by 17.4 mm, and 100% by 19.5 mm. Based on the results of the study and the data analysis, it can be concluded that several concentrations of ethanol extract of Karuk leaf affect the growth of M. furfur in vitro.